Using functional genomics to provide insights into social parasitism by Cape honey bee clonal workers based on mandibular gland pheromones (Apis mellifera capensis Eschscholtz) - Crewe, Robin M. (University of Pretoria, 2024)
Thesis (PhD (Entomology))--University of Pretoria, 2019.